PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, PELATIHAN KERJA, DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. VIVO ELEKTRONIKA CB. PLAZA MEDAN FAIR - Elfin Apriani Zebua; Hendry Hendry (Jurnal Manajemen Terapan dan Keuangan, 2021)
Employee work problems are things that deserve special attention by members of the organization. The purpose of this study is to determine the effect of job training, transformational and compensation, either simultaneously or partially. This research uses quantitative descriptive analysis method. The population in this study were all employees obtained as many as 139 people the sampling technique used the Slovin formula to obtain as many as 92 people as the research sample test. The data analysis technique used F-Test, T-Test, and Multiple Linear Regression. From the results of data processing, it is known that the transformational leadership variable (X1) partially has a significant and positive effect on the work productivity of PT. Vivo Elektronika Cb employees. Plaza Medan Fair. The work variable (X2) partially has a significant and positive effect on the work productivity of PT. Vivo Elektronika Cb employees. Plaza Medan Fair. The compensation variable (X3) partially has a significant and positive effect on the work productivity of PT. Vivo Elektronika Cb employees. Plaza Medan Fair. Keywords: Transformational Leadership, Job Training, Compensation, and Productivity.